Marital status and living condition as predictors of mortality and readmissions among African Americans with heart failure. (1st November 2016) - Lu, Marvin Louis Roy; Davila, Carlos D.; Shah, Mahek; Wheeler, David S.; Ziccardi, Mary Rodriguez; Banerji, Sourin; Figueredo, Vincent M.
Abstract: Socioeconomic factors, including social support, may partially explain why African Americans (AA) have the highest prevalence of heart failure and with worse outcomes compared to other races. AA are more likely to be hospitalized and readmitted for heart failure and have higher mortality. The purpose of this study is to determine whether the social factors of marital status and living condition affect readmission rates and all-cause mortality following hospitalization for acute decompensated heart failure (ADHF) in AA patients. Methods: Medical records from 611 AA admitted to Einstein Medical Center Philadelphia from January, 2011 to February, 2013 for ADHF were reviewed. Patient demographics including living condition (nursing home residents, living with family or living alone) and marital status (married or non-married -including single, divorced, separated and widowed) were correlated with all-cause mortality and readmission rates. Results: In this cohort (53% male, mean age 65 ± 15, mean ejection fraction 32 ± 16%) 25% (n = 152) of subjects were unmarried. Unmarried patients had significantly higher 30-day readmission rates (16% vs. 6% p = 0.0002) and higher 1-year mortality (17% vs. 11% p = 0.047) compared with married patients. Fifty percent (n = 303) of subjects were living with family members, while 40% (n = 242) and 11% (n = 66) were living alone or in a nursing facility, respectively. Patients living with family members had significantly lower 30-day readmission rates when compared with those living alone or in a nursing facility (7% vs 21% vs. 18% p = < 0.0001). Furthermore, they had the lowest 1-year mortality (14% vs 32% for nursing facility patients and 17% for those living alone (p = 0.0007). After controlling for traditional risk factors (age, gender, body mass index, peak troponin I, left ventricular ejection fraction, B-type natriuretic peptide, hypertension, diabetes mellitus, hyperlipidemia, and coronary artery disease), being married was an indpendent predictor of 1-year mortality (OR 0.50 p = 0.019) and living alone for 30-day readmission (OR 2.86 p = < 0.001). Conclusion: The socioeconomic factors of marital status and living condition significantly correlated with mortality and 30-day readmission rate in AA heart failure patients. Specifically, being married and living with family independently predict lower mortality and fewer readmissions. Surprisingly, living in a nursing facility was associated with significantly higher mortality than living alone or with family.